SOLUTION THERMODYNAMICS OF TRICLOSAN AND TRICLOCARBAN IN SOME VOLATILE ORGANIC SOLVENTS - DELGADO, Daniel R.; HOLGUÍN, Andrés R.; MARTÍNEZ, Fleming (Vitae, 2012)
Thermodynamic functions of Gibbs energy, enthalpy, and entropy for the solution processes of the antimicrobial drugs Triclosan and Triclocarban in five volatile organic solvents were calculated from solubility values at temperatures from 293.15 to 313.15 K. Triclosan and Triclocarban solubility was determined in acetone, acetonitrile (AcCN), ethyl acetate (AcOEt), methanol (MetOH), and cyclohexane (CH). The excess of Gibbs energy and the activity coefficients of the solutes were also calculated. The Triclosan solubilities were greater than those of Triclocarban in all the solvents studied. At 298.15 K the solubility diminished for Triclosan in the order, acetone > AcOEt > AcCN > MetOH > CH, while it diminished for Triclocarban in the order, acetone > AcOEt > MetOH > AcCN > CH. On the other hand, thermodynamic quantities relative to the transfer process of these drugs from CH to all other organic solvents, as well as from water to organic solvents for Triclosan were also calculated in order to estimate the hydrogen-bonding contributions.